Morphological and phylogenetic characterization of fungi within Hymenochaetales: introducing two new species from southern China. (17th November 2021) - Luo, Xi; Chen, Yu‐Hui; Zhao, Chang‐Lin
Abstract : Two new wood‐inhabiting fungal species, Lyomyces niveus and L. ochraceoalbus spp. nov. are proposed based on a combination of morphological and molecular evidence. Lyomyces ochraceoalbus is characterised by resupinate basidiomata with tuberculate, cracking hymenial surface, clavate basidia with a median constriction, gathering numerous irregular crystals, and thin‐walled basidiospores with one or two globules. Lyomyces niveus is characterised by resupinate basidiomata, smooth to grandinioid hymenial surface, presence of three kinds of cystidia, and broadly ellipsoid basidiospores. Sequences of the ITS and nLSU gene regions were generated, and phylogenetic analyses were performed with maximum likelihood, maximum parsimony and Bayesian inference methods. The phylogenetic reconstruction of Schizoporaceae based on a concatenated ITS+nLSU dataset showed that the two new species are nested in Lyomyces . A second phylogenetic analysis, of the genus Lyomyces, demonstrated that multiple isolates of L. niveus forms a monophyletic lineage which is sister to a clade comprising L. crustosus, L. juniperi, L. ochraceoalbus and L. vietnamensis . Moreover, L. ochraceoalbus is closely related to L. crustosus .